The Business of Hope Professional Fundraising in Neoliberal Canada - Raddon, Mary-Beth.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book contributes to research on the ascendance of neoliberalism in Canada through the vantage point of professional fundraising in the 1990s and 2000s. Fifty high-ranking fundraisers from across Canada were interviewed through 2008 and 2009 about changes they had witnessed since starting their careers. Fundraising as an occupation was burgeoning in this period in response to the devolution of state responsibility across the major domains of nonprofit activity: education, health care, social services, the arts, recreation, overseas humanitarian activities, and environmental protection. Welfare state retrenchment left the nonprofit and voluntary sector competing for private sources of funding with the help of these newly hired expert staff. As fundraisers worked to instill a culture of philanthropy, while targeting the ultra-rich and advocating for tax-favourable treatment of major gifts, they became both products and promoters of the neoliberal political and cultural reconstruction of Canadian society. Mary-Beth Raddon is Associate Professor at Brock University in St. Catharines, Ontario, Canada. She is the current chair of the Department of Sociology and a former graduate program director of the MA in Social Justice and Equity Studies. She is a qualitative researcher in the field of economic sociology.
Chapter 1. Introduction: The Business of Hope -- Chapter 2. The (3z(BDo or Die(3y (BProject of Creating a Culture of Philanthropy -- Chapter 3. (3z(BIn the Business to Change Lives(3y(B: Fundraising as a Neoliberal Vocation -- Chapter 4. The Generosity Gap: Canadian Fundraisers$1 (BCross-National Comparisons -- Chapter 5. (3z(BWe Have to Fit the Men in Somewhere(3y(B: Explaining Gender Inequality in Fundraising -- Chapter 6. (3z(BI Have to Be Optimistic; I$1 (Bm a Fundraiser(3y(B: Professional Fundraising and the Politics of Hope -- Appendix: Research Methods.s
Keywords: Political sociology; Economic sociology; Industrial sociology; Industries; Political Sociology; Economic Sociology; Sociology of Work; Industries